Maslinic Acid Therapeutic Effect in Rheumatoid Arthritis Through Activation of Nuclear Factor Erythroid 2 and Suppression of Nuclear Factor Kappa B as well as Apoptotic Markers - Darwish, Ahmed Mohamed; Alqahtani, Saeed Mohammed; Bashir, Salah Omar; Zafrah, Hind Awad; Dawood, Amal Fahmy; Sabir, Deema Kamal; Morsy, Mahmoud Mohamed; Al-Daher, Hamzeh Ahmed; Morsy, Mohamed Darwesh; Mohamed, Muataz Elsiddig; Agamy, Dalia Fathi El (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Rheumatoid Arthritis (RA) is a chronic autoimmune condition characterized by persistent joint inflammation, resulting in pain, stiffness and degradation. Despite advances in understanding RA pathophysiology, its precise mechanisms remain complex. This article explores the processes involved in RA, including the interplay of inflammatory cascades, immune responses, cytokines and apoptosis. Materials and Methods: This study divided 32 Wistar rats into five groups. The model group (RA) received Collagen type II (COII) injections into both knee joints. The Maslinic Acid treated (MA) model group including the COII+MA group received (i.p) daily MA treatment and COII+MA+brusatol which received both MA and brusatol (a selective Nrf2 inhibitor) daily. Controls received vehicle solutions and a control-treated group received MA. The study assessed in blood and synovial tissues Rheumatoid Factor (RF), the inflammatory (NF-κB p65, TNF-α, IL-6, VEGF and ICAM) and oxidative stress (ROS, MDA, SOD and GSH) pathways, nuclear factor erythroid 2-Related Factor 2 (Nrf2) and biomarkers of apoptosis and survival (Bax, cleaved caspase-3 and Bcl-2) gene expression levels. Results: Induction of RA by COII caused the modulation of inflammation and oxidative stress as well as Nrf2, NF-κB p65 and apoptosis, which were inhibited by MA. On the other hand, all the protective effects of MA were substantially blocked by the pharmacological inhibitor of Nrf2, brusatol. Conclusion: Maslinic acid provides profound protection in a rat model of RA via Nrf2 activation in association with the inhibition of oxidative stress, inflammation and apoptosis
Keywords: Apoptosis; Maslinic Acid; Rheumatoid Arthritis